Investing in S-REITs (hospitality, healthcare, industrial and data centre) - Liu, ShuYuan (Nanyang Technological University, 2022)
REITs (Real Estate Investment Trusts) are collective investment schemes that invest in a portfolio of income-generating real estate assets such as retail malls, offices, hotels, and serviced apartments, with the goal of providing income to unitholders. REIT assets are professionally managed, and the assets' revenues (mainly rental income) are usually paid to existing shareholders at regular intervals. REIT investment objectives are similar to those of stock investments: steady income supplement and long-term capital growth potential. This report will discuss the use of fundamental analysis (FA), news analysis (NA), and technical analysis (TA) in the selection and trading of REITs, as well as the efficacy of FA+NA+TA in outperforming the market.